2009
DOI: 10.1111/j.1365-2133.2009.09353.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusand hand eczema severity

Abstract: Staphylococcus aureus was present on hands in almost half of all patients with HE, and was significantly related to severity of the disease. This association indicates that S. aureus could be an important cofactor for persistence of HE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
46
5
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 30 publications
(60 reference statements)
11
46
5
10
Order By: Relevance
“…The severity of hand eczema correlates to the presence of Staphylococcus aureus [6], but the cause and effect relationship has not been clearly investigated. Knowledge on S. aureus colonization rates and epidemiology in hand eczema is limited [6,7]. Recent studies have however shown that more than 70 % of AD patients are colonized with S. aureus in skin lesions [8,9], often associated with clinical signs of secondary infection [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The severity of hand eczema correlates to the presence of Staphylococcus aureus [6], but the cause and effect relationship has not been clearly investigated. Knowledge on S. aureus colonization rates and epidemiology in hand eczema is limited [6,7]. Recent studies have however shown that more than 70 % of AD patients are colonized with S. aureus in skin lesions [8,9], often associated with clinical signs of secondary infection [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Sampling for bacterial culture from one or several sites from the hands is usually done with a cotton swab [6]. To obtain a more representative sample of the bacterial flora on the entire hand, the Bglove juice^method has been shown to give reliable and valid results [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these countries the SA colonization rates were between 80% -100% [24,25]. However, SA colonisation rates in healthy Sri Lankan individuals (13%) were comparable to the rates reported in healthy European individuals (6-30%) [26]. Although, SA colonization rates were lower in AD patients in Sri Lanka, the presence of genes encoding SAg in SA isolates were similar to those from countries with a high prevalence.…”
Section: Discussionmentioning
confidence: 71%
“…При этом обнаружена корреляция между степенью колонизации золотистым стафилококком и тяже-стью течения экземы. Таким образом, носительство S. aureus является значимым кофактором в патоге-незе экземы кистей [7].…”
unclassified